Life Cycle Assessment of a multi-use offshore platform: Combining wind and wave energy production. (15th November 2017) - Elginoz, Nilay; Bas, Bilge
Abstract: Due to increasing demand in the use of ocean space for energy and food production, multi-purpose use of marine areas is under concern. Here, a novel semi-submersible floating platform, which unites wave and wind energy converters, is investigated in terms of environmental sustainability. LCA is a methodology, to assess environmental burdens of a product/function including all the phases it experiences, which makes it a perfect tool to determine environmental burdens of renewable energy systems due to their considerably lower impacts during operation. In this study, LCA of an energy farm, constituted of multi-use offshore platforms was executed. Results showed manufacturing of the platform is the main source of pollution. In the manufacturing phase; fixed, moving and mooring parts are the main contributors and the WECs make a minor contribution. Material consumption is the main source for burdens during the life cycle of the system hence recycling ratios considered at the end of life scenarios affect the overall results. Implementation of multi-use floating concept to different locations gives various results changing with the capacity factor and the distances. The comparison between semi-submersible system and the spar platform ended up with comparable results both in terms of environmental burdens and material consumption. Highlights: LCA of a multi-use offshore platform design for Atlantic conditions is executed. Manufacturing of the platform is the biggest source of pollution. Wave energy converters has a small contribution on environmental burdens. Results of the study are sensitive to the recycle ratio. Results of the study are sensitive to the location of the energy farm.